String‐Vacuous Head Movement in Japanese: New Evidence from Verb‐Echo Answers. (15th December 2017) - Sato, Yosuke; Hayashi, Shintaro
Abstract: Whether Japanese has verb raising or not has been one of the most contentious issues in the literature for more than 20 years. This Remark presents novel evidence for string‐vacuous head movement from the previously unexplored perspective of verb‐echo answers. We propose that such an answer form in Japanese is derived through V–T–C movement in overt syntax, followed by TP ellipsis at Phonological Form (PF), rejecting the alternative pro ‐drop analysis. Our analysis is supported by a wide range of new facts on verb‐echo answers, including the indefinite pro ‐drop restriction, the impossibility of voice mismatches, and adverb‐inclusive interpretations. Because our theory presupposes head movement as its central analytical premise, the results of this article indicate that Japanese grammar is equipped with string‐vacuous verb raising. We will also briefly explore some curious behaviors of verb raising in Japanese relating to the scope of negation under ellipsis and intervention effects. We will argue that this phenomenon differs fundamentally from its counterpart in European languages such as French in that the former is an optional operation in narrow syntax that only occurs if it yields new outcomes at PF and/or Logical Form (LF).